A partial heating supercritical CO2 nested transcritical CO2 cascade power cycle for marine engine waste heat recovery: Thermodynamic, economic, and footprint analysis. (15th December 2022) - Wang, Zhe; Jiang, Yuemao; Ma, Yue; Han, Fenghui; Ji, Yulong; Cai, Wenjian
Abstract: A novel cascade system, in which the exhaust CO2 residual heat from a partial heating supercritical CO2 (SCO2 ) power cycle is reclaimed by a transcritical CO2 (TCO2 ) power cycle, is developed for onboard engine exhaust gas waste heat recovery. Firstly, thermodynamic analysis of the cascade system is carried out with the investigation of pinch points in heat exchangers. Then the influence of the topping cycle on the heat source condition of the bottom cycle is found, and the parametric study of the cascade system is performed from the viewpoint of thermodynamics, economy, and footprint. Further, the system comparison analysis with single-optimization is carried out to prove the superiority of the proposed system. Finally, the three-objective optimization is performed to maximize power output, minimize heat exchanger area per unit power and levelized cost of electricity. The results indicate that by integrating a TCO2 power cycle with the partial heating SCO2 cycle, system thermodynamic performance can increase by 15.35%. The recuperator effectiveness has a great impact on the bottoming cycle heat source temperature. The total heat recovery efficiency of the proposed system is improved by 22.64% and 20.24% respectively, compared with the simple SCO2 -TCO2 combined cycle and the recuperative SCO2 -TCO2 combined cycle. The multi-objective optimization results of the system performance are 841.84 kW, 0.2028 m 2 /kW, and 7.434 cent/kWh, respectively, with the 136 °C discharge temperature of the exhaust gas and 29.26% thermal efficiency. These results confirm the cascade system is attractive to waste heat recovery engineering, especially in space-constrained applications. Highlights: A partial heating SCO2 nested TCO2 cascade power cycle is proposed for waste heat recovery. Energy, exergy and pinch point analyses are conducted for the cascade system. Thermodynamic connection between the top and bottom power cycle is explored. Comparison analysis is carried out to prove the superiority of the cascade system. Optimization is performed from thermodynamic, economic and footprint viewpoints.